Family medicinal plant cultivation facility (SABDA TOGA: Sarana Budidaya Tanaman Obat Keluarga) for urban areas in RT 04 and RT 06 RW 07, Tegalrejo Salatiga - Yohanes Martono; Andreas Setiawan; Slamet Widodo (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
The limited land owned by the community in urban areas such as RT 04 and 06 RW 07 in the Tegalrejo village in Salatiga makes the Family Medicinal Cultivation Facility (SABDA TOGA) one of the solutions so that the com-munity can continue to grow crops that can be used for daily needs. Through community service (PM), training on how to apply aquaponics planting technology, herbal plants in sacks (taherlarung) and fermentation of organic liquid fertilizer as a TOGA planting model in urban communities. The method used is making demonstration plots for the application of organic aquaponics planting media technology, taherlarung, and fermentation of or-ganic liquid fertilizer for TOGA plants in the partner environment, carrying out data collection on TOGA plants in the community, and conducting socialization in the community. The results of this dedication show that aqua-ponics planting media technology can be combined with a fish pond so that it can produce organic TOGA. Aqua-ponics technology can be automated and can also take advantage of the people's narrow land with a vertical media arrangement pattern. TOGA planting in taherlarung can be increased to become an alternative way of decorating the road. While liquid organic fertilizer is very potential to be produced in large quantities because it utilizes household organic waste with a fermentation period of approximately 1 month. Some people already have TOGA plants but do not know the benefits and how to use them. This PM activity shows that aquaponics, taherlarung and fermentation of organic liquid fertilizer are suitable for TOGA weaving in urban communities. Some urban community groups tend to not know and utilize TOGA.